Preparation and kinetic studies of a new antibacterial sodium alginate gelatin hydrogel composite - Reem A. ElTatawy; Amel M. Ismail; Mohammed Salah Ayoup; Magda M. F. Ismail; Howida Abouel Fetouh (Scientific Reports)
Abstract This study involved synthesis of a novel antibacterial heterocyclic compound, sodium 2-(2-(3-phenyl-1, 2, 4-oxadiazol-5-yl) phenoxy) acetate abbreviated as Na-POPA. Further development of a biocompatible, pH-responsive hydrogel drug carrier prepared utilizing the natural polymers gelatin and sodium alginate. The compound loaded on the hydrogel represented new drug delivery system. Comprehensive characterization of Na-POPA was performed using Fourier-transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance (¹H NMR), carbon-13 nuclear magnetic resonance (¹³C NMR), and high-resolution mass spectrometry (HRMS). The compound was loaded onto the sodium alginate/gelatin hydrogel carrier under feasible experimental conditions. The successful incorporation of Na-POPA into the hydrogel matrix was confirmed via scanning electron microscopy (SEM), powder X-ray diffraction (pXRD) analysis and FT-IR spectroscopy. Cytotoxicity assays revealed that the all the loaded and unloaded compound induced cell toxicity at large concentration much lower than many reported results. The hydrogel reduced the inherent cytotoxicity of Na-POPA and enhanced its biocompatibility. The release kinetics of Na-POPA from the hydrogel were evaluated spectrophotometrically at different pH conditions simulating biological fluids. The release rate at pH 1.2 was greater than the release at pH 6.8, with a higher cumulative release observed at pH 6.8. The release kinetics obeyed the pseudo-second-order kinetic model, indicating a controlled release mechanism influenced by the hydrogel’s physicochemical properties. Electrochemical impedance spectroscopy and cyclic voltammetry further confirmed that the compound release was pH-dependent. The high swelling and solubility at pH 6.8 enhance the release. The larger amount released at 6.8 (target intestine) because of more solubility, leaching and swelling rather than shrinking.